Adverse Events of Electronic Moxibustion Treatment for Knee Osteoarthritis: Case Reports and a Literature Review - Yoona Oh; Jisun Lee; Yeonhak Kim; Eun Seok Kim; Kun Hyung Kim; Byung Ryul Lee; Gi Young Yang (MEDrang Inc., 2022)
Background Electronic moxibustion has the advantage of temperature control and maintenance, and overcomes the limitations of the existing moxibustion process without the use of the combustion process. However, as the application of electronic moxibustion in clinical practice has increased, safety issues are emerging. Methods Clinical cases of electronic moxibustion treatment for knee osteoarthritis where burns occurred were collected. In addition, adverse events reported in clinical studies using electronic moxibustion for patients with knee osteoarthritis were collected from studies retrieved from Korean and international databases. Results There were 3 cases of superficial 2nd degree burns retrospectively collected through chart reviews. Among the selected 5 studies for literature review, 2 studies reported adverse events which were burns milder than those reported in these 3 cases in this retrospective case review. Conclusions Since the risk of superficial 2nd degree burn was discovered in the cases reviewed, further research on safe electronic moxibustion treatment is required without compromising the effectiveness of moxibustion.